Gonadal structure and androgen activity of the male lesser mouse deer (Tragulus Javanicus Osbeck) - Sriyanto, . (2011)
The lesser mouse deer (Tragulus javanicus), belongs to the suborder Ruminantia and as the smallest ungulate species in the world is a common native to the tropical rain forest of Southeast Asia. The population of lesser mouse deer is threatened by illegal hunting and habitat destruction for many years. Thus, conservation and management of this animal is becoming important. One of the keys for successful conservation and breeding of wild animals is the management and knowledge of the reproductive system. Currently, limited information is available on the reproductive physiology of the lesser mouse deer. Furthermore, the reproductive physiology with regards to the reproductive activity of the lesser mouse deer is mainly unknown, creating gaps in understanding the reproduction of this animal. As there is limited information on their reproductive especially of the male animal, this study was conducted with the objective to determine the gross morphological and histological features on the male reproductive organs, the testosterone levels and profiles, the distribution and appearance of steroidogenic enzymes and the gonadal regulatory hormones in the testis to provide better understanding on the male reproductive activity of lesser mouse deer. This study describes the general structures of the male reproductive system of lesser mouse deer, which include gross and histological morphology, analysis of testosterone concentration levels and the profile, based on the testosterone levels in fecal samples. The samples were collected from 3 adult male lesser mouse deer for a period of 6 months covering both dry and wet months. They were subjected to high performance liquid chromatography (HPLC) techniques to determine the testosterone levels. Using immunohistochemistry staining, distribution and localization of gonadal regulatory hormones, sex steroid hormones and converting steroidogenic enzymes in the testis were determined. Generally, the male reproductive organ consisted of two oval-shaped testes, 14 mm in length and 10 mm in diameter, which were located within the scrotum. This was followed by the ducts that consisted of the epididymis and vas deferens of 117 mm long, and the accessory organs consisted of ampullae, seminal vesicles, prostate and bulbo-urethral glands, and finally the penis. The penis of lesser mouse deer was fibroelastic type with sigmoid flexure, resembling that of the boar and other ruminants. The glans penis was twisted at the end, resembling that of the boar but was twisted one and a half turns clockwise whereas the twisted end of the glans penis of boar is counter-clockwise. The study of testosterone profile revealed fluctuating testosterone levels between 0.01 and 17.90 ppm, but the levels were significantly increased (p<0.05) in the wet months. Peak testosterone levels were observed at approximately 10-day intervals, particularly during the wet months of October, November and December, which correlated well with the 16-day estrus cycle of the females. These results were supported by investigation on the immunolocalization of steroidogenic enzymes and gonadal hormones in the testis of the lesser mouse deer during dry and wet months. Testicular steroidogenesis of the lesser mouse deer occurs at different sites within a testis. The 3-HSD enzyme appeared in Leydig cells, Sertoli cells and spermatogonia while the cytochrome P450scc enzyme appeared only in the Leydig cells. The inhibin alpha hormone, on the other hand, was observed stronger in Sertoli cells. This suggests that in the wet months, Leydig cells are more active in producing steroidogenic enzymes and gonadal hormone, thus, correlated well with earlier observations that the breeding season for the lesser mouse deer was during the wet months. On the other hand, Sertoli cells were active in producing the enzyme in both dry and wet months.